Toward an integrated approach to food security and nutrition in Cambodia - Chanrith, Ngin; De Silva, Sanjiv; Sithirith, Mak; Sok, Sao (WorldFish, 2024)
Food production in Cambodia’s Tonle Sap Lake floodplain requires a more integrated approach to water and land use and a greater focus on nutrition, noting that around 33 percent of Cambodia’s population is malnourished (UNICEF 2023). This includes malnutrition rates among children under 5 years, which are the highest in the region. Addressing nutrition gaps critical for human development and productivity in Cambodia is urgent given the current impacts of climate change on agricultural production and productivity. The climate-induced decline and unpredictability of such crucial resources as water and land have caused increasing competition and conflicts among different users. If this is to be reduced, policies on water-land governance need to be better coordinated and local resource planning and management need an integrated resource-use approach.